Purification of a PHA-Like chitin-binding protein from Acacia farnesiana seeds: A time-dependent oligomerization protein - Santi-Gadelha, T.; Rocha, B. A. M.; Oliveira, C. C.; Aragao, K. S.; Marinho, E. S.; Gadelha, C. A. A.; Toyama, M. H. [UNESP]; Pinto, V. P. T.; Nagano, C. S.; Delatorre, P.; Martins, J. L.; Galvani, F. R.; et al. (Humana Press Inc, 2008)
A lectin-like protein from the seeds of Acacia farnesiana was isolated from the albumin fraction, characterized, and sequenced by tandem mass spectrometry. The albumin fraction was extracted with 0.5 M NaCl, and the lectin-like protein of A. farnesiana (AFAL) was purified by ion-exchange chromatography (Mono-Q) followed by chromatofocusing. AFAL agglutinated rabbit erythrocytes and did not agglutinate human ABO erythrocytes either native or treated with proteolytic enzymes. In sodium dodecyl sulfate gel electrophoresis under reducing and nonreducing conditions, AFAL separated into two bands with a subunit molecular mass of 35 and 50 kDa. The homogeneity of purified protein was confirmed by chromatofocusing with a pI=4.0+/-0.5. Molecular exclusion chromatography confirmed time-dependent oligomerization in AFAL, in accordance with mass spectrometry analysis, which confers an alteration in AFAL affinity for chitin. The protein sequence was obtained by a liquid chromatography quadrupole time-of-flight experiment and showed that AFAL has 68% and 63% sequence similarity with lectins of Phaseolus vulgaris and Dolichos biflorus, respectively.
Keywords: Acacia farnesiana; lectin-like protein; purification; oligomerization; tandem mass spectrometry